Biocontrol and growth enhancement potential of Trichoderma spp. on broad leaf mustard - Paudel, Vipassana; Pathak, Rajiv; Lamichhane, Janardan; Gauchan, Dhurva P. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Microbial isolates from plant associated habitats are being considered as valid alternatives to synthetic pesticides. The aim of the study was to select beneficial fungi belonging to Trichoderma genus, to be added as soil inoculants, in order to develop an innovative, economic and suitable alternative to synthetic fertilizers for growth promotion of plants. The isolated Trichoderma were characterized and identified by morphological and microscopic analysis. The antagonistic effects of these Trichoderma isolates were tested against three pathogenic fungi; Sclerotinia minor, Fusarium oxysporum and Fusarium solani. Dual culture technique was employed and percentage of inhibition (I %) on mycelial growth of pathogenic fungi was calculated. Isolates BC and KB, showed the highest antagonistic effect against S. minor by 100%. Isolate DH and TH showed partial suppression of F. solani y 64.74% and 70.94% respectively. Isolates HA and Y restrain F. oxysporum by 85.12% and 85.90% respectively. Hence, BC, KB, DH, TH, HA, and Y could be a potential bio-control agent, BCA. In vitro and in vivogrowth promotion study was carried out by seed treatment method.Isolate EO revealed highest growth promotion activity in all parameters. In vitro studies of seedling assay indicated that isolate EO exhibited best effect on almost all the parameters; root length, shoot length, plant wet weight, plant dry weight, germination percentage and seedling vigour index in in vitro condition. However, greenhouse studies indicated that GS showed highest shoot length, TH promoted highest root length and HA showed maximum number of leaves. Significant difference was observed inroot length in greenhouse experiment and plant wet weight in seedling assay at p≤0.05. The results presented in this study further reinforce the concept of biological control and plant growth promotion by Trichoderma as an alternative disease control strategy. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 1, 2017, Page: 85-94